New information technologies of automation of designing and research of nonlinear deformations of plates of designs - Слободян, Я.О.; Гузь, А.В.; Кудря, Ю.С. (Proceedings of National Aviation University (archive), 2004)
The results of numerical researches of experimental models of plates of designs with application of new information technologies of automation of designing are given on the basis of a program complex LIRA also estimation of an error of linear account in comparison with results of the decision of a nonlinear task step-by-step method and finite element method.